The Therapeutic Value of Bone Marrow-Derived Endothelial Progenitor Cell Transplantation after Intracerebral Hemorrhage in Rats - Zhang, Rui; Yang, Jing; Yuan, Jingjing; Song, Bo; Wang, Yan; Xu, Yuming (Frontiers in Neurology, 2017)
Abstract Aims: To study the effect of endothelial progenitor cell (EPC) treatment on intracerebral hemorrhage (ICH) in rats and elucidate possible mechanisms. Method: The rats were randomly divided into 3 groups: 1) EPC group: ICH + EPC, 2) PBS group: ICH + PBS, and 3) Sham group. EPCs were transplanted intravenously 6 h after ICH. Modified neurological severity score (mNSS) was used to evaluate neurological function. Blood-brain barrier (BBB) integrity was evaluated. Dead cells, inflammatory cytokines, and neuroprotective cytokines were assessed to investigate possible mechanisms. Results: The animals in the EPC group showed significant improvement in neurological function at 48 h, 72 h, and 7 d after ICH, compared with those in the PBS group. EPC transplantation significantly reduced brain edema and the number of dead cells in the hematoma boundary areas. The intensity of Evans Blue was decreased, and expression levels of ZO-1 and claudin-5 were increased in the EPC group. Proinflammatory cytokines, including IFN-γ, IL-6, and TNF-α, were decreased, whereas anti-inflammatory cytokines, including TGF-β1 and IL-10, were increased in the EPC group. In addition, expression levels of BDNF, VEGF, and NGF were increased following transplantation of EPCs. Conclusion: EPC transplantation could improve neurological function of ICH rats. The protective effect may be mediated by promotion of neuroprotective cytokine secretion, restoration of the BBB, reduction of cell death, and the decrease in inflammation.